A Clash of Kings - Martin, George R. R. (A Song of Ice and Fire ; Game of thrones)
HBO's hit series A GAME OF THRONES is based on George R. R. Martin's internationally bestselling series A SONG OF ICE AND FIRE, the greatest fantasy epic of the modern age. A GAME OF THRONES is the first volume in the series